Absence of fibroin H sequences and a significant divergence in the putative fibroin L homolog in Neomicropteryx cornuta (Micropterigidae) silk - Imada, Yume; Rouhova, Lenka; Zurovcova, Martina; Hradilova, Miluse; Podlahova, Sarka; Sehadova, Hana; Zurovec, Michal (Communications biology, 2025)
Micropterigidae is regarded as the sister group of all the other Lepidoptera, providing important insights into the evolution of Lepidoptera. However, the gene and protein profiles of silk from Micropterigidae have not yet been identified. In this study, we investigate the components of silk cocoons of the micropterigid species Neomicropteryx cornuta. Here we show that the protein fibroin heavy chain (FibH) is absent in the silk of N. cornuta and that the putative homolog of fibroin light chain (FibL) is also absent or severely altered. This is confirmed by transcriptome and genome analyses of the conserved regions in this species. The examination of the synteny around the fibH genes in several Lepidoptera and Trichoptera species shows that the genomic region containing this gene is absent in another micropterigid species, Micropterix aruncella. In contrast, we found putative orthologs of fibH and fibL in the representative transcripts of another distinct clade, Eriocraniidae. This study shows that the loss of FibH and the loss or severe divergence of FibL occurrs specifically in the family Micropterigidae and reveals dynamic evolutionary changes in silk composition during the early evolution of Lepidoptera. It also shows that silk proteins without FibH can form a solid cocoon.
Keywords: Animals; hedvábí; můry; sekvence aminokyselin; Fibroins; Moths; hmyzí proteiny; Evolution, Molecular; Amino Acid Sequence; molekulární evoluce; fibroiny; Phylogeny; Lepidoptera; transkriptom; Insect Proteins; zvířata; Transcriptome; fylogeneze; Silk